Importance of the Investment Projects destined for the National and Paranormal Games in Ibagué, and the impact that I present the irregularities of these resources in the year 2015 (2017)
The bill of the General Budget of the Nation contemplates the destination of resources for the investment projects, there we find a very important item destined for socio cultural purposes, as the financing of the programs of adaptation of the facilities for the National Games and Paranormal that are celebrated every 4 years. In the twentieth version and celebration that would take place, exactly in the department of Tolima, the objective was not achieved. The resources destined for the execution of this project, unfortunately were diverted their funds, the works that were initially being carried out were left unfinished, leaving the department in deficit and the municipality of Ibagué without sports facilities. In the development of the following document a socio - economic and political analysis will be carried out; And the importance of these sporting events for the country and the consequences of the bad management in the last games in 2015, specifically the events that occurred in the city of Ibagué.